HUBUNGAN ADVERSITY QUOTIENT (AQ) DENGAN KESIAPAN TERHADAP INTERPROFESSIONAL EDUCATION (IPE) PADA MAHASISWA PROFESI FK UGM - , CHAIRUNNISA RAHMATINA; , Mariyono Sedyowinarso, S.Kp., M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background : IPE was the process by which a group of students from the health-related occupations with different backgrounds learn together to interact each other and share the knowledge that they have. This was important for improving collaboration in health care provider and improve patient well-being. In practice, this process may affected with many kind of factors. One of that factors is Adversity Quotient (AQ). AQ is the ability that people have to turn the obstacle that they have into the opportunity. Objective : This study aimed to determine the correlation between Adversity Quotient (AQ) and readiness of Interprofessional Education (IPE) in clinical student of Faculy of Medicine Gadjah Mada University (FM GMU). Methods : This was descriptive analytic correlational study with quantitative approach and applied cross sectional design. The subjects were 76 medical student and nursing student in clinical stage. The subjects were choosen by quota sampling method. Quantitative data were obtained through ARP (Adversity Response Profile) questionnaire for AQ level and RIPLS (Readiness Interprofessional of Learning Scale) questionnaire for readiness level. Result : The result of the study showed that the majority of FM GMU clinical student (46 or 60,5%) had high level of AQ (climbers transition). The readiness of IPE mostly belonged in high level (64 or 84,21%). There was no correlation between AQ level and readiness of IPE with p value 0,208 (p>0,05). Conclution : Both of FM GMU clinical student AQ and readiness level, majority were on high level. There showed no difference AQ and readiness level between FM GMU medical and nursing clinical student. There was no correlation between AQ level and readiness of IPE in FM GMU clinical student.